Yamaha Electronic Manufacturing (M) Sdn Bhd. / Amirah Husna Rosli - Rosli, Amirah Husna (Universiti Teknologi MARA, Perlis, Faculty of Business and Management, 2021)
Yamaha Electronic Manufacturing (M) Sdn. Bhd. has given me lots of wonderful and useful memories during my 6-month industrial training. In this report, I have written the company’s profile such as business core, organizational chart, vision, mission, goals and also their product offered. The company’s primary business is the manufacturing of audio equipment, professional audio and network equipment products service parts centre for home entertainment. Next, in the training reflection, I have mentioned I was assigned to be in the Human Resource department. The experience working in the company has made me improve in a lot of new things such as my soft skills and computer skills as I completed all the tasks given by my supervisor. The company also has offered me intrinsic and extrinsic benefits such as allowance, certificates and learned how to use their software on checking the daily attendance. Furthermore, in order to complete the company analysis, I used financial ratios analysis and SWOT analysis to measure the company’s performance as a whole. Due to the private and confidential matter of YEM company, this report will be using Formosa Prosonic Industries Berhad’s financial statement as a reference to analyze the company performance by using the trend analysis 2015 to 2019. The company has good liquidity position and efficient in utilizing its assets into sales but the company is high financial risk as the business is funded by debt. The profitability ratios also show an inconsistent trend as they do not manage to gain more profits even their sales is high. Moreover, this report also used SWOT analysis to analyze its current situation by internal strengths, internal weaknesses, external opportunities, and external threats. Therefore, discussion and recommendation can be made as the company analysis is ready which aim to improve the company business growth and performance that is affected by some issues and problems. As a conclusion, the process of completing this report has made me understand more about how Yamaha works as a whole. All the experiences and knowledge gained in the company exposed me to the reality of the working environment in the industry which opened my mind. In future, hope this internship experience will guide me to survive in the industry.